Rudolf Arnheim’s Art Psychology includes Chinese images: From “T’ai-chi tu” to Others - Wan-Ting Yu (Modern Perspectives in Language, Literature and Education Vol. 5, 2021)
By using Chinese images as T’ai-chi tu, Rudolf Arnheim’s Gestalt art theory investigates visual perceptual forces and the phenomenon of "isomorphism" in psychological movement. He draws attention to the similarities between western and Chinese aesthetic conceptions by bringing up these Chinese instances. To compensate for the shortcomings of western mind, he employs Chinese ideas, particularly Taoism.Taoist thought led him on a new path, allowing him to critically reflect on western dichotomies that strongly split perception from thinking, and art from science. In order to complement western experience and create a universal empirical aesthetic theory, Arnheim explores Chinese art from the viewpoint of western psychology and also focuses on western ideas using Chinese culture as a mirror.